Addition of [18F]Fluorodeoxyglucose Positron Emission Tomography With Computed Tomography to Cross‐Sectional Imaging Improves Staging and Alters Management in Hepatocellular Carcinoma. Issue 6 (8th May 2020) - John, Binu V.; Aubuchon, Sean; Dahman, Bassam; Konjeti, Venkata Rajesh; Heuman, Douglas; Hubert, Jennifer; Thomas, Smitha; Deng, Yangyang; Solomon, Cynthia; Sundaram, Latha Thankam; Love, Eleanor; Singal, Amit G.; et al.
Abstract : In this work, we characterize the value of positron emission tomography (PET) with computed tomography (CT) in combination with cross‐sectional imaging for staging and prognostication of hepatocellular carcinoma (HCC) patients. In this retrospective cohort study, HCC patients underwent PET‐CT after initial staging with contrast‐enhanced CT or magnetic resonance imaging (MRI). The benefit of PET‐CT was measured by the identification of new HCC lesions, and potential harm was quantified by the number of false positives and subsequent diagnostic evaluation. We used multivariate Cox regression analysis to evaluate the association between the highest grade on PET‐CT with the risk of extrahepatic metastasis, progression‐free, and overall survival. Among 148 patients, PET‐CT detected additional extrahepatic metastasis in 11.9% of treatment‐naïve and 13.8% of treatment‐experienced patients. PET‐CT changed the Barcelona Clinic Liver Cancer (BCLC) staging in 5.9% of treatment‐naïve and 18.8% of treatment‐experienced patients compared with CT/MRI alone, changing HCC management in 9.9% and 21.3% of patients, respectively. Of the patients, 5% (n = 8) experienced severe physical harm requiring additional procedures to evaluate extrahepatic findings. High tumor grade on PET‐CT was independently associated with a higher likelihood of extrahepatic metastasis (hazard ratio [HR], 17.1; 95% confidence interval [CI], 3.6‐81.5) and worse overall survival (HR, 2.4; 95% CI, 1.4‐4.3). Treatment‐experienced patients (versus treatment‐naïve patients; HR, 9.7; 95% CI, 1.9‐49.4) and BCLC stage A (HR, 8.2; 95% CI, 1.5‐45.9; P  < 0.01) and BCLC stage B (HR, 20.6; 95% CI, 1.5‐282.2; P  < 0.05) were more likely to have an upstaging with PET‐CT compared with BCLC stage C (reference). PET‐CT provides prognostic information and improves tumor staging beyond CT/MRI alone, with subsequent changes in management for patients with HCC.